1993
DOI: 10.1177/0887302x9301100304
|View full text |Cite
|
Sign up to set email alerts
|

Company Demographics as an Influence on Adoption of Quick Response by North Carolina Apparel Manufacturers

Abstract: Quick Response has proven financial benefits, but less than one half of U.S. apparel manufacturers have implemented it. This study investigated apparel manufacturers' demographics as related to adoption of Quick Response. Two hundred and three North Carolina apparel manufacturers were sent a mailed questionnaire, resulting in a 48% (N = 66) adjusted return rate.Factor analysis reduced the 17 Quick Response statements to 5 factors. Multivariate analysis of variance and one-way analysis of variance were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…Efforts to increase product quality were noted by the number of total quality management programs and the rise in statistical process control procedures implemented by apparel manufacturers and other FTAR companies during the 1970s and 1980s (Cooper, 1980(Cooper, -1981; Georgia Institute of Technology, 1980). Later in the 1980s, the Quick Response (QR) effort was initiated as the importance of predicting the right fashion and producing the right product for the final consumers was raised with further improvements in efficiency (AAMA, 1987; Kincade & Cassill, 1993 In the first decade of the 2000s, companies have instituted programs for consumer responsiveness, often called consumer-centric manufacturing, by adapting more quickly to market changes and by providing individualized responses to consumers (Pan & Holland, 2006).…”
Section: Apparel Manufacturersmentioning
confidence: 99%
“…Efforts to increase product quality were noted by the number of total quality management programs and the rise in statistical process control procedures implemented by apparel manufacturers and other FTAR companies during the 1970s and 1980s (Cooper, 1980(Cooper, -1981; Georgia Institute of Technology, 1980). Later in the 1980s, the Quick Response (QR) effort was initiated as the importance of predicting the right fashion and producing the right product for the final consumers was raised with further improvements in efficiency (AAMA, 1987; Kincade & Cassill, 1993 In the first decade of the 2000s, companies have instituted programs for consumer responsiveness, often called consumer-centric manufacturing, by adapting more quickly to market changes and by providing individualized responses to consumers (Pan & Holland, 2006).…”
Section: Apparel Manufacturersmentioning
confidence: 99%
“…Each must communicate commitment to QR as well as the implications of that commitment to all involved. The managements must instil trust and confidence in the strategy and between all the personnel of the organizations that interface with this strategy, including merchandising, buying, shipping and receiving, inventory control and accounting staffs [6,7].…”
Section: Quick Response Partnershipsmentioning
confidence: 99%
“…To determine if the usable responses were representative of the total sample, Chisquare tests (goodness-of-fit, single sample) were calculated and confirmed that the sample was representative for number of employees and products produced by SIC code (Marascuilo & McSweeney, 1967). Although the response rate was low, comparable studies (Dickerson, Dalecki, & Meyer, 1991;Kincade & Cassill, 1993) had fewer numbers available for statistical analysis.…”
Section: Resultsmentioning
confidence: 99%